2016
DOI: 10.1080/15548627.2015.1136770
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-mediated autophagy regulates proliferation by targeting RND3 in gastric cancer

Abstract: LAMP2A is the key protein of chaperone-mediated autophagy (CMA), downregulation of LAMP2A leads to CMA blockade. CMA activation has been implicated in cancer growth, but the exact mechanisms are unclear. Elevated expression of LAMP2A was found in 8 kinds of tumors (n=747), suggesting that LAMP2A may have an important role in cancer progression. Unsurprisingly, LAMP2A knockdown in gastric cancer (GC) cells hindered proliferation, accompanied with altered expression of cell cycle-related proteins and accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 51 publications
2
92
1
Order By: Relevance
“…19,20 However, like other autophagic pathways such as macroautophagy, 6,36,37 the contribution of CMA to cancer cell proliferation and tumor growth seems to be context dependent. Thus, studies in other types of cancer cells have proposed a negative effect of CMA on cancer cell biology through degradation of oncogenic proteins such as TP53 protein 38,39 or HK2 (hexokinase 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, like other autophagic pathways such as macroautophagy, 6,36,37 the contribution of CMA to cancer cell proliferation and tumor growth seems to be context dependent. Thus, studies in other types of cancer cells have proposed a negative effect of CMA on cancer cell biology through degradation of oncogenic proteins such as TP53 protein 38,39 or HK2 (hexokinase 2).…”
Section: Discussionmentioning
confidence: 99%
“…7 Thus, CMA inhibition in malignant cells lowers cellular proliferation and reduces tumorigenic and metastatic capacity. 7,19 Later reports have confirmed this dependence on CMA for cancer cell growth and attribute it to a diversity of mechanisms including: protection against oxidative damage, 19 removal of negative regulators of cell proliferation 20 and antioncogenes 21 or maintenance of the metabolic switch favorable for cancer cell growth. 22,23 However, the role of CMA on early stages of tumor development such as transformation of normal cells into cancerous cells has not been elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…The cellular pathways and physiological importance of CMA in cancer still needs to be delineated 91 . It has been reported that high basal CMA activity is a common feature among different types of human tumors 92 . In contrast to normal cells, this upregulation of CMA occurs independent of the macroautophagy status of cancerous cells.…”
Section: General Aspects Of the Unfolded Protein Responsementioning
confidence: 99%
“…CMA may also improve resistance to various stress inducing stimuli including chemotherapy [56], ER stress [57] and hypoxia [58,59]. Lastly, CMA may contribute to tumor cell proliferation and metastatic potential [52,[60][61][62]. While constitutively active CMA was frequently found in cancer cells [52], a study reported that the lack of Lamp2A expression in mice increased the risk of malignant transformation and liver tumorigenesis [63].…”
Section: Autophagy In Cancermentioning
confidence: 99%